Breaking the Intergenerational Cycle of Stunting in Indonesia: A Life-Course and Policy Perspective - Dida Wanti (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Stunting remains a persistent public health challenge in Indonesia, threatening the country’s human capital development and long-term economic growth. Although national strategies have emphasized interventions during the first 1,000 days of life, evidence suggests that stunting is rooted in intergenerational and life-course factors that begin long before pregnancy. This article aims to analyze the intergenerational pathways of stunting in Indonesia using a life-course perspective and to assess the alignment of national policies with this framework. A narrative review and policy analysis were conducted using peer-reviewed literature published between 2010 and 2025, as well as key national policy documents related to stunting reduction. The findings indicate consistent evidence linking adolescent anemia, early pregnancy, maternal undernutrition, and low birth weight to increased risk of childhood stunting. Despite strong political commitment, policy implementation remains fragmented, with limited emphasis on preconception and adolescent health interventions. Current strategies tend to focus on downstream interventions rather than upstream prevention. Strengthening integrated, multisectoral policies targeting critical life stages particularly adolescence and preconception is essential to break the intergenerational cycle of stunting. A comprehensive life-course approach is crucial to accelerate sustainable stunting reduction and support Indonesia’s vision for human capital development toward 2045.